2006
DOI: 10.1111/j.1744-6155.2006.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Research Review: Effective School‐Based Childhood Overweight Interventions

Abstract: Social Cognitive Theory and the role of social learning are useful when designing interventions for preventing and treating childhood overweight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 26 publications
(60 reference statements)
0
61
0
2
Order By: Relevance
“…19 Several systematic reviews of childhood obesity programs have been published. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] With the exception of one recent review 20 and an earlier review conducted by our team in collaboration with the Community Guide Branch of the Center for Disease Control and Prevention (CDC), 25 this work is unique in that it focuses specifically on studies undertaken in schools. Previous reviews have focused solely on the prevention of obesity 22 or weight loss interventions among already overweight children.…”
Section: Introductionmentioning
confidence: 99%
“…19 Several systematic reviews of childhood obesity programs have been published. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] With the exception of one recent review 20 and an earlier review conducted by our team in collaboration with the Community Guide Branch of the Center for Disease Control and Prevention (CDC), 25 this work is unique in that it focuses specifically on studies undertaken in schools. Previous reviews have focused solely on the prevention of obesity 22 or weight loss interventions among already overweight children.…”
Section: Introductionmentioning
confidence: 99%
“…According to the NTT, transportation into a narrative world is believed to lead to acceptance of persuasive messages within a story through multiple mechanisms [24,25,26]. The NTT also suggests that images are most impactful when they are embedded in a story rather than provided in isolation as it could enhance the narrative influence [27]. Therefore, visual images relevant to the story's message, such as those incorporated in manga comics, may further impact attitudes and beliefs.…”
Section: Theoretical Basis and Content Of Intervention Incmentioning
confidence: 99%
“…Research by Cole et al (2006) found that programs consisting of a curriculum incorporating lifestyle habits, nutrition education, and physical activity may encourage positive behavioral changes in children. They suggested however, that these child-based interventions must consider the child"s social context, which includes the school, community, and home environment.…”
Section: Problem Statementmentioning
confidence: 99%
“…In addition, effective interventions for weight loss in obese children have been shown to be successful when parents and adult caregivers are motivated and understand their role in establishing healthy eating habits among their children (American Academic of Pediatrics, 2003;Golan & Crow, 2004;Must et al, 1992). In response, the development of partnerships between schools and community agencies to provide familybased interventions has been suggested (Cole et al, 2006;Evans et al, 2011;Foster et al, 2008). However, there have been limited systematic follow-up evaluations of the effectiveness of such programs in changing families" nutrition and fitness habits after the completion of programs (Gonzalez-Suarez, Worley, Grimmer-Somers, & Dones, 2009;Story, 1999).…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation